PENERAPAN MEDIA GAMBAR UNĽUK MENINGKAĽKAN KEĽERAMPILAN MEMBACA PADA PELAJARAN BAHASA INDONESIA SISWA KELAS II SDN CIKUYA 01 KAB.BANDUNG - Esti Ayu Fatimah; Undang Sudan; Arif, Muhammad (JURNAL ARMADA PENDIDIKAN, 2023)
The low interest of students in Indonesian language lessons causes most students to be less enthusiastic about following the lessons delivered by the teacher. Improving Indonesian reading skills with media images is the teacher's effort to increase student interest. Under these conditions the teacher tries to improve learning by carrying out classroom action research. The purpose of this study was to determine the increase in reading skills using media images in class II students at SDN Cikuya 01. The results showed that in each cycle there was progress, it was proven that in the first cycle, students' interest reached 65% in learning and students who completed learning in cycle I new ( 42.4%). In cycle II there was an increase in student interest, namely (77%). While student learning outcomes are increasing with mastery learning reaching (89.8%). This proves that through the media of images students can solve their own problems in reading skills in Indonesian lessons so that student learning outcomes increase.